The impact of urban parks on the thermal environment of built-up areas and an optimization method - Yujun Yang; Yuheng Lv; Dian Zhou (PLoS ONE, 2025)
Rapid urbanization, while transforming people’s living environments, also brings a series of urban issues such as the urban heat island effect. The urban park is an effective means to alleviate the urban heat island effect in summer. How to make better use of the cold island effect formed by urban parks to improve the urban outdoor thermal environment is an important topic. This manuscript takes Xi’an as the research area, using remote sensing data as the data source and combining field surveys, to explore the cooling characteristics of the cold island effect in the urban built-up area. It is demonstrated that, the influencing factors of the cooling effect of urban park cold islands are summarized: the area and perimeter of the park, the area and perimeter of water bodies, and the area of trees are all positively correlated with the cooling effect. The surrounding building density and building plot ratio are also positively correlated with the cooling effect of the green space. A comprehensive scoring model for each influencing factor is established, and the principal component analysis method is used to determine the weight of each indicator on the cooling effect of park design elements, among which the area of green space parks has the greatest influence weight. The demand space for cold islands in Xi’an’s parks is analyzed, and optimization strategies and suggestions for improving the urban thermal environment are put forward from both inside and outside the park.